Choices in vaccine trial design in epidemics of emerging infections. - Rebecca Kahn; Annette Rid; Peter G Smith; Nir Eyal; Marc Lipsitch (PLoS Medicine)
In a Policy Forum, Marc Lipsitch and colleagues discuss trial design issues in infectious disease outbreaks.